2014
DOI: 10.1128/jvi.03678-13
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Infection Induces Indoleamine 2,3-Dioxygenase Expression in Human Monocyte-Derived Macrophages through p38/Mitogen-Activated Protein Kinase and NF-κB Pathways: Impairment in T Cell Functions

Abstract: Epstein-Barr virus (EBV) infection has been observed in tumor-infiltrated macrophages, but its infection effects on macrophage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 41 publications
7
57
0
Order By: Relevance
“…Furthermore, while TGFβ inhibits IFNγ -induced IDO1 mRNA expression in cultured fibroblasts, TGFβ induces IDO1 expression in pDCs [113,117]. Finally, whereas IL-6 inhibits IDO1 in CD8α + murine DCs, the inflammatory cytokine acts in concert with TNFα to induce IDO1 in virus-infected human monocytederived macrophages [94].…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, while TGFβ inhibits IFNγ -induced IDO1 mRNA expression in cultured fibroblasts, TGFβ induces IDO1 expression in pDCs [113,117]. Finally, whereas IL-6 inhibits IDO1 in CD8α + murine DCs, the inflammatory cytokine acts in concert with TNFα to induce IDO1 in virus-infected human monocytederived macrophages [94].…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 97%
“…Activation of the NF-κB pathway is important for the induction of IDO1 in response to stimuli other than IFNγ (Figure 2), including LPS [92], GpC-ODNs [107], viral infection [94,108,109] and CD80/CD86 ligation [101]. For example, induction of IDO1 by LPS and virus infection involves the activation of both NF-κB and p38 MAPK (mitogen-activated protein kinase) [92,94].…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Liao et al (27) used NPC cell lines to detect that IL-6 promoted NPC cell proliferation in a dose-and time-dependent manner, and this was accompanied by increasing cyclin D1 and Bcl-2 expression, STAT-3 activation, and inhibition of Bax and p21 expression. Liu et al (28) observed that in certain macrophages of the tumor stroma of NPC tissue, IL-6-and TNF-α-dependent expression of tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase led to suppressed proliferation of T cells and impaired cytotoxic activity of CD8(+) T cells, thus facilitating immune escape.…”
Section: Discussionmentioning
confidence: 99%